A bumpy road to success (or not) : The case of Project Genesis at Nevada DMV - Dhillon, Gurpreet (2022)
This paper presents findings from the implementation of an integrated information system, Project Genesis, at Nevada Department of Motor Vehicles (DMV), USA. While the development and implementation was riddled with problems, the project was still labeled as successful. The case study identifies a range of issues in the organization and evaluates these based on different interpretations of various stakeholders. In a final synthesis, a contextual analysis of the emergent issues is conducted. Considerations for defining and managing the relative success of an implementation are presented.